Efeito do exercício físico no equilíbrio e no metabolismo oxidativo-inflamatório de ratos tratados com vincristina - Sagrillo, Luiza Minato (2015)
The Vincristine is a chemotherapy used for various types of cancers, and is one of the major side effects the impairment of motor function and balance, as well as the oxidative and inflammatory unbalance. Therefore, the present study aimed to evaluate the effect of physical exercise on the balance and in the oxidative metabolism of rats treated with anti-inflammatory Vincristine. For this, rats weighing between 270-300 g were divided into two groups: Trained Group (n = 20, 6 weeks of swimming, 1:00/day, 5 days/week, with 5% overload body weight) and Sedentary Group (n = 20, placebo swimming in a tank with water to 5 cm deep, with no extra charge). After 6 weeks the two groups (n = 20 of each) were treated with a single dose of weekly 0, 5 mg/kg of vincristine sulfate, for two weeks, totaling a cumulative dose of 1 mg/kg intraperitoneal. The rats used in control groups (n = 10 n = 10 trained and sedentary) received the same dose of saline (NaCl). For analysis of motor function and balance were performed after chemotherapy applications, on 1, 7, 8,15 days: Rotarod tests (balance), Grip Test (muscle strength), the Open field (exploration) and the hot plate (peripheral sensitivity). At the end of the assessment (day 15) cerebellum samples were taken for analysis of oxidative stress (DCFH, SOD and CAT) and blood samples for analysis of Picogreen and CBC. In behavioral assessment, there was a decrease in body balance in rats exposed to the VCR and, also, a significant protection of physical exercise. There was no significant decrease in muscle strength and exploitation in the open field of rats exposed to VCR, but there was no effect per se of physical exercise, which increased muscle strength and the distance and the operating time standing in the open field in mice. There was significant change in peripheral sensitivity in mice treated and prior exercise was able to normalize this damage. In biochemical analysis we observed a significant protective effect of exercise in trained/VCR rats, once ROS levels were reduced (DCFH analysis) and antioxidant system enzymes of the cerebellum SOD and CAT modulated positively. In the analysis of observed Picogreen exercise protection against DNA damage in the trained/VCR group. The CBC trained /VCR rats they kept the parameters analyzed within the reference values when compared to sedentary/VCR. Therefore, the exercise proved to be a great ally in protecting the body and balance the immune system front of chemotherapy toxicity Vincristine.